Perancangan Situs Web Jasa Tour and Travel Erza Travel dengan Mengadaptasi Human Centered Design - Dinar Indah Dwi Utami; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Internet now has an important role, because by accessing the internet, people can find useful information according to their needs. Therefore, organizations are competing to use the internet media to support their operational activities in increasing the income of the organization. Erza Travel is one of the organizations engaged in the transportation of car rental service providers. Erza Travel is currently just starting their business. So they want to expand their business by building a website so that other public people know the existence of Erza Travel. The purpose of this study is to design a user interface travel website that can facilitate the user in using it. One method that can be used in designing a website user interface that allows users one of them is by using Human Centered Design. Stages performed in this research are (1) define and specify the context of use by defining stakeholders related (2) specifiy user requirements consisting of functional and non-functional requirements and modeled using use cases with RUP Style (3) designing design solutions derived from user requirements (4) evaluating designs that have been designed taking into user opinions made with interview with the users (5) improve the design solution that has been given feedback by the user. The result of this research is got the context of use where there are two main users from Erza Travel website that are potential customer and admin of Erza Travel. Needs obtained through interview with the user that is as much as 7 points. The result of the design solution is a wireframe designed based on user needs and design guidance. Design evaluation is done after the design is completed and done with interview technique with the user and got some suggestion, which then do the improvement of design according to suggestion submitted by user.